2015
DOI: 10.1093/hmg/ddv472
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association analysis identifies three new susceptibility loci for childhood body mass index

Abstract: A large number of genetic loci are associated with adult body mass index. However, the genetics of childhood body mass index are largely unknown. We performed a meta-analysis of genome-wide association studies of childhood body mass index, using sex- and age-adjusted standard deviation scores. We included 35 668 children from 20 studies in the discovery phase and 11 873 children from 13 studies in the replication phase. In total, 15 loci reached genome-wide significance (P-value < 5 × 10(-8)) in the joint disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
280
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 281 publications
(312 citation statements)
references
References 46 publications
24
280
2
2
Order By: Relevance
“…From the original papers it can be seen that the instrument for adult BMI is stronger than for the other traits (the respective R 2 for adult BMI, birthweight, child BMI and WHR, are: 0.027, 0.008, 0.020 and 0.013; the R 2 for child BMI is only for the three novel SNPs but, as the authors of the original paper point out, it was calculated on a relatively small sample and needs to be treated with some caution). 14 , 18–20 Interestingly, although Gao et al. use the most up-to-date BMI GWAS data, 20 they do not do the same for WHR, despite the most recent GWAS for WHR adjusted for BMI identifying 33 additional variants (as well as confirming the 14 used here from the earlier GWAS) and being published around the same time as the most up-to-date BMI GWAS.…”
Section: The Provenance Of Adult Bmi Effects With Cancers and Other Pmentioning
confidence: 99%
“…From the original papers it can be seen that the instrument for adult BMI is stronger than for the other traits (the respective R 2 for adult BMI, birthweight, child BMI and WHR, are: 0.027, 0.008, 0.020 and 0.013; the R 2 for child BMI is only for the three novel SNPs but, as the authors of the original paper point out, it was calculated on a relatively small sample and needs to be treated with some caution). 14 , 18–20 Interestingly, although Gao et al. use the most up-to-date BMI GWAS data, 20 they do not do the same for WHR, despite the most recent GWAS for WHR adjusted for BMI identifying 33 additional variants (as well as confirming the 14 used here from the earlier GWAS) and being published around the same time as the most up-to-date BMI GWAS.…”
Section: The Provenance Of Adult Bmi Effects With Cancers and Other Pmentioning
confidence: 99%
“…Since these two studies, there has been a boom in GWAS studies and subsequent obesity susceptibility loci identified. To date, ~200 variants associated with obesity-related phenotypes have been identified; however, it is postulated that these loci only account for <10% of the variance [10][11][12][13][14][15]. Although this is quite low, and means that 90% of variance remains to be explained, they have provided us with an emerging wealth of knowledge of the genomic localisation, frequency and effect sizes, and potential functional implications that these loci may have.…”
Section: Genome-wide Association Studies In Obesitymentioning
confidence: 99%
“…Protective effects of Faim2 in cultured neurons have also been described for Purkinje cells and cortical neurons 7,10 . In addition these neuronal effects, Faim2 single nucleotide polymorphisms (SNPs) have been linked to an increased susceptibility for obesity, especially in childhood, in a genome wide association study (GWAS) 11 . For certain subpopulations, i.e.…”
Section: What Do We Know About Faim2?mentioning
confidence: 99%